Effects of single and successive applications of rice husk charcoal on paddy soil carbon content and rice productivity during two cropping seasons. Issue 2 (4th March 2019) - Koyama, Shinichi; Hayashi, Hisayoshi
ABSTRACT: A two-year field experiment was conducted to evaluate residual and cumulative effects of rice husk charcoal (RC) application on physicochemical soil properties and rice productivity in an Andosol paddy field. Three RC application rates, 10, 20, and 40 Mg ha −1, one rice husk (RH) application rate of 20 Mg ha −1, and a control with no application of RC or RH were laid out in the first year of the experiment. In the second year, the experimental plot was divided into halves: one with the same application rates as in the first year (successive applications) and the other without additional RC or RH (single application). Significant impacts of RC application were observed from the first year on soil bulk density, porosity, carbon (C) content, and carbon-to-nitrogen (C/N) ratio. Soil C content was directly proportional to the amount of RC application over the 2 years showing that the C derived from RC was markedly recalcitrant in soil compared to that from RH. The increased C was present not only in the plow layer but also spread over the top 20 cm of paddy field. As compared to the control, successive RC applications at 20 Mg ha –1 increased soil C contents by 12.7 g kg –1 and 14.4 g kg –1 in the 0–10 cm and 10–20 cm layers after two rice seasons, respectively. Successive RC applications significantly increased straw weight and panicle number, partly due to the increased Si uptake by rice plants. However, grain yield did not significantly differ among the treatments because RC application decreased 1000-grain weight. We speculate that the reduction in 1000-grain weight may be due to immobilization of available N at the reproductive stage under high soil C/N ratio conditions. This suggests the need for N fertilizer top-dressing to obtain the potential yield in the RC-applied fields. Furthermore, the diminishing residual effects of RC application on the rice growth and yield parameters in the second season suggest that successive, or applications at an interval of 2–3 years, would be required to maintain the higher Si deposits in plants, thereby sustaining rice productivity.